Potentially avoidable emergency department transfers from residential aged care facilities for possible post‐fall intracranial injury. (25th July 2022) - Tulchinsky, Igor; Buckley, Richard; Meek, Robert; Lim, Joel Jun Yi
Abstract: Objectives: To determine the percentage of potentially preventable residential aged care facility (RACF) to ED transfers for potential intracranial injury post‐fall. To describe rates of CT brain (CTB) performance, intracranial trauma‐related findings, neurosurgical intervention, and patient outcome. Methods: Patient lists were obtained from the hospital electronic medical record, screened for eligibility and data abstracted. Potentially preventable was defined as: (1) RACF return from ED within 24 h, regardless of CTB performance or finding; (2) ED management could reasonably have been provided at the RACF. Comparisons between those with CTB performed or not, including external signs of craniofacial trauma, anticoagulant medication use, baseline cognitive impairment and presence of an advanced care directive (ACD) were made. Results: Of 784 patients, 415 (53%) were classified as potentially avoidable. Of these, 314 (76%) had a CTB. Of all 784 patients, 538 (69%) had a CTB performed. CTB was more likely with presence of external signs of craniofacial trauma (26% [95% CI 23–30] vs 20% [95% CI 15–25], P < 0.001) and anticoagulant use (59% [95% CI 55–63] vs 42% [95% CI 37–49], P < 0.001) but not for presence of cognitive impairment or ACD. From the 538 CTBs, 31 (6%) patients had acute intracranial trauma‐related findings with all having conservative management. None of the 11 (1%) deaths were in the potentially preventable subgroup. Conclusion: Just over half of the RACF to ED transfers were classified as 'potentially avoidable'. Abstract : Residential aged care facility (RACF) residents are frequently transferred to EDs due to concern of possible intracranial injury post‐fall. We found that although CT brain (CTB) performance was common, over half of these transfers were potentially avoidable, since patients returned to their RACF without active management, regardless of CTB findings.